Successful Radical Pneumonectomy for a Primitive Neuroendodermal Tumor in the Lung: A Case Report and Review of the Literature - Yue, Bingqing; Chen, Peng; Yin, Pan; Wang, Jiankai; Liu, Fanying; Zhao, Duo; Chen, Jingyu; Jiang, Hua (Frontiers in Surgery, 2021)
Peripheral primitive neuroendodermal tumors (PNETs) and Ewing’s sarcoma belong to the Ewing family of tumors and are small round-cell malignancies originating from spinal cord cells. These tumors account for 5% of all small round-cell malignant neoplasms. PNETs that arise from the lung parenchyma without pleural or chest wall involvement are very rare. We report a case of an adult female with a large pulmonary PNET who had given birth just 1 month prior to the diagnosis. She had cough and expectoration for 6 months, and the preoperative examination showed no metastases. Thus, we performed radical pneumonectomy and lymph node dissection. The patient recovered well without surgical complications and was discharged 7 days after the surgery. Postoperative pathology confirmed that the tumor was a small round-cell malignancy, and the tumor cells were positive for CD99, Friend leukemia virus integration 1 (FLI-1), and neuron-specific enolase (NSE), which was consistent with the diagnosis of a PNET. For primary large pulmonary PNETs, radical pneumonectomy may be a safe surgical method, worthy of further application in clinical practice.